Beliefs About Medicine and Glycemic Control Among Type 2 Diabetes Patients: A Cross-Sectional Study in West Bank, Palestine - Maher R. Khdour; Heba B. Awadallah; Mustafa A. Alnadi; Doaa H. Al-Hamed (SAGE Publishing, 2020)
Introduction: To examine the mean differences between patient beliefs about medicine with reference to adherence and glycemic control. Methods: This study utilized a cross-sectional questionnaire-based approach. Adherence to medication was measured with the Morisky Green Levine Medication Adherence Scale (MGLS); glycemic control as the last HbA1c test value; and beliefs about medicine with the Beliefs about Medicines Questionnaire (BMQ). Results: According to MGLS scale, 220 (57.9%) of the diabetic patients were classified as high adherent to their medications and 160 (42.1%) were classified as low adherent. Patients had strong believes in their medication, the mean necessity score was significantly outweighed the mean concerns score (17.7 vs 14.4; P  < .001). Low adherent patients had significantly more concerns about long term effect of medications (14.4 vs 13.8; P  < .008). No significant mean differences were found between glycemic controlled and uncontrolled group regarding necessity or concern domains. Conclusion: Assessing beliefs about medicine is crucial for recognizing patients at risk of low adherence, which offers a way to help patients with diabetes to achieve a better glycemic control.